Two-Channel Gettering of Recombination-Active Impurity in Polycrystalline Solar Silicon - Litovchenko, V.G.; Naseka, V.M.; Evtukh, A.A. (Ukrainian Journal of Physics, 2012)
The features of the recombination-active impurity gettering in polycrystalline silicon have been studied. The research method included the formation of a porous silicon layer 0.5–2 μm in thickness on the backside of a silicon wafer, the deposition of aluminum layer 0.5–1 μm in thickness, and the thermal annealing at 700–950 ºC during 30–60 min. The corresponding gettering model has been proposed, which includes the diffusion of iron atoms by means of two most probable independent channels: in the wafer bulk and along the grain boundaries. By comparing the theoretical results and experimental data, we established that 30% of gettered impurity atoms diffuse with a high rate along the grain boundaries, and 70% of them in the grain bulk.